SIFAT FISIKA MEKANIKA PAPAN SEMEN PURUN TIKUS (Eleocharis dulcis) PADA BERBAGAI PENGERAS (The physical and mechanics properties of mouse purun cement board on various hardeners): Renhart Jemi1 , Yusurum Jagau2 , Yanetri Asi Nion2 , Trisna Anggreini2 , Ria Anjalani2 , Dessy Natalia Koroh1 , Endra Cipta3 , Apri Wijaya Putra4 , Krisna Wahyu4 - Administrator Journal (HUTAN TROPIKA, 2018)
ABSTRACKThe research objective was to determine the properties of physical and mechanics of mousepurun cement board on various hardeners. The cement board was processed with a size of 30 cmx 30 cm x 2 cm, a ratio of 3: 1, a density of 2 g / cm2, purified water content of 15%, hardenerCa(OH)2, CaCl2, MgCl2 with a concentration of 2%. Before making the cement board thehydration temperature test is carried out, then the resulting board is tested for the physicalproperties of the mechanics. And the grave test for 3 months. Data averaged and SD thentabulated and written in graphical form. The results of the study were hydration temperature:31.38-33.50oC, inhibiting factors: 6.94-10.19%, board water content: 13.55% - 15.77%; density:1.07-1.16 g / cm2; MoR: 22.96 - 30.31 kg / cm2, Compressive strength: 0.84 - 3.34%.Conclusion: Mouse purun can be processed into cement board. The good nature of the cementboard is to treat CaCl2 2% hardener.Keywords: Purun, cement board, hardener, hydration and MoR